Dana Pihak Ketiga dan Modal Sendiri terhadap Financing to Deposit Ratio di PT Bank BRI Syariah - Setia, Mochamad Nur Rahmat; Magi, Bahmid I; Nuraeni, Eni (Universitas Ma'soem, 2021)
This research was conducted because the development of TPF and Equity Capital at PT Bank BRI Syariah for the 2016-2020 period fluctuated. TPF in 2016 in the third quarter and fourth quarter experienced an increase but FDR decreased as well as fluctuations in TPF during 2018 and 2020 which did not match the theory, where the higher the DPK collected, the greater the distribution of financing so that the FDR value would increase and vice versa. This study aims to determine the effect of TPF on FDR, the effect of Equity Capital on FDR, the effect of TPF and Equity Capital simultaneously on FDR at PT Bank BRI Syariah. This study uses associative quantitative research, with the object of this research being Third Party Funds, Own Capital and Financing to Deposit Ratio at PT Bank BRI Syariah. The type of data used is secondary data in the form of financial ratios published by PT. Bank BRI Syariah starting from the period 2016 to 2020. The population in this study is the financial statements of PT Bank BRI Syariah. The sample used is the quarterly published financial statements of BRI Syariah Bank for the period 2016 to 2020. The data analysis used is multiple correlation analysis, multiple regression analysis, coefficient of determination analysis, t-test and F-test. Own capital has a positive and significant effect on FDR. TPF and own capital simultaneously have a positive and significant effect on FDR at PT Bank BRI Syariah.